Pelatihan Personality Development dan Keterampilan Komunikasi Kepemimpinan Remaja di Kampung Sejahtera Kota Medan - Sigit Hardiyanto; Zulfahmi Zulfahmi; Agung Saputra; Faizal Hamzah Lubis; Arifin Saleh; Abrar Adhani; Fadhil Pahlevi Hidayat (University of Muhammadiyah Sumatera Utara, 2023)
The community partnership program with the title Personality Development and Leadership Communication Skills for Youth in Kampung Sejahtera Medan City is to provide knowledge of soft skills in terms of developing communication skills for adolescents in Kampung Sejahtera, Petisah Tengah Village, Medan Petisah Subdistrict, Medan City. This activity was carried out at the Kampung Sejahtera river school hall, Jalan KH. Zainul Arifin, Medan City. The implementation of this activity is carried out in the first week and end of July 2022. The method of implementation in this activity program is using lectures, group discussions, and mentoring for youth in order to improve soft skills of personality characteristics, good personality, good performance, and skills and abilities. skills in communication. The results of the activities that have been carried out in this community partnership program have provided a positive response for the youth activity participants, such as high enthusiasm in participating in the activities. In addition, some that appear that are often encountered can be given an explanation from program implementers that can increase youth's knowledge regarding the development of communication skills and skills.